TRANSFORMING ACCOUNTANCY EDUCATION IN SCHOOLS-COMPETENCY BASED EDUCATION AND ASSESSMENT - Chaudhary, Upasana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With the introduction of National Education Policy 2020 the teaching, learning, and assessment done in the school education has changed. This transformation brings about the changes in the conventional style of the teaching and conceptualization of concepts to the skills and competency based education. The NCERT formulated the National Curriculum for School Education which provides suggestive curriculum for the teachers to introduce this transformation from traditional way of teaching in School Education to competency based education. NCERT also drafted Learning outcomes for Foundational to Secondary Stage for teachers enabling in implementing and incorporating the new competency based education, as suggested by National Education Poilcy,2020. Assessment aligned with new competency based education also underwent transformation in the new competency based education. It is no longer considered one time activity in testing the memory or factual recall but it is actually considered as a continuous ,regular and formative to give us an insight on what exactly students are learning and to make improvements on the teaching strategies. Competency-based assessment seeks to measure what the students know as well as their ability to utilize the knowledge and skills in diverse environments.